P-43 Capacity assessment for advance care planning in older people with cognitive impairment. (1st September 2015) - Kiriaev, O; Chacko, Emme; Jurgens, JD; Ramages, Meagan; Malpas, P; Dyall, Lorna; Cheung, G
Abstract : Background: People with dementia receive worse end of life care compared to those with cancer. The main barrier to undertaking advanced care planning (ACP) in people with dementia has been uncertainty about their capacity to engage in such discussions. Although a capacity screening tool specific to advance care planning could improve its uptake within this population, none as yet exist. Aim: The primary aim of this study was to compare the ACP-CAV tool (Advance Care Planning – Capacity Assessment Vignette) to the assessment of capacity to engage in ACP using a semi-structured interview adapted from the MacArthur Competence Assessment Tool-Treatment (MacCAT-T). The secondary aim was to identify other variables that may predict whether a person has capacity to engage in ACP. Methods: 37 Participants (mean age = 83.9; mean MMSE = 26.5) were recruited from two large retirement villages with different levels of care. Participants completed the Mini Mental State Examination (MMSE), Trail Making Tests and Geriatric Depression Scale before undertaking the capacity assessments which were video recorded to enable further analysis by 4 independent old age psychiatrists. Results: The ACP-CAV correctly assessed the capacity of 65% of the cases when compared to the MacCAT-T method. MMSE was the only variable found to predict capacity. Conclusion: Capacity assessment should be routinely conducted prior to discussing ACP with older people, in particularly those with cognitive impairment. However, it is a complex iterative process that does not easily lend itself to screening methodology and requires a high level of clinical judgement.